2004
DOI: 10.1021/la049455i
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Crystal Phases of Charged Colloidal Platelets

Abstract: The liquid crystal phase behavior of a suspension of charged gibbsite [Al(OH)3] platelets is investigated. By variation of the ionic strength, we are able to tune the effective thickness-to-diameter ratio of the platelets in suspension. This enables us to experimentally test the liquid crystal phase transition scenario that was first predicted a decade ago by computer simulations for hard platelets (Veerman, J. A. C.; Frenkel, D. Phys. Rev. A 1992, 45, 5632), that is, the isotropic (I) to nematic (N) and isotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
132
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(143 citation statements)
references
References 38 publications
11
132
0
Order By: Relevance
“…This phenomenon can be explained by a simple osmotic compression model. 21,22 Using equations of state obtained from literature and from Monte Carlo computer simulations that we performed, we find good agreement with the experimentally determined individual phase heights.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…This phenomenon can be explained by a simple osmotic compression model. 21,22 Using equations of state obtained from literature and from Monte Carlo computer simulations that we performed, we find good agreement with the experimentally determined individual phase heights.…”
Section: Introductionsupporting
confidence: 77%
“…When sedimentation-diffusion equilibrium is reached, Eq. ͑1͒ describes the complete system: 21,22 Ϫ ͩ ‫ץ‬⌸ ‫ץ‬n ͪ ‫ץ‬n ‫ץ‬z ϭm*gn. ͑1͒…”
Section: Model a Sedimentation-diffusion Equilibriummentioning
confidence: 99%
“…From computer simulations by Veerman and Frenkel [37], and later Zhang et al [38], it was found that hard platelets may also form another liquid-crystal phase, namely the orientationally and 2D translationally ordered columnar (C) phase. This phase has also been observed experimentally in suspensions of sterically stabilised and charged colloidal plates [39][40][41]. There is a very interesting issue, raised in one of these reports [39], which is related to the inherent size polydispersity in these synthetic suspensions: it is quite surprising that such systems, with a rather high polydispersity of up to 25%, show the columnar liquid-crystal phase.…”
Section: Introductionmentioning
confidence: 68%
“…In a polydisperse GO dispersion, large GO sheets generate excluded volume for small sheets giving rise to entropic rearrangement to form long range ordering resembling a liquid crystalline state. The critical theoretical volume fraction (Φ) for the transition between isotropic to nematic phase can be calculated based on Equation 1 which served as a model system for liquid crystal phases of charged colloidal platelets, [21,22] …”
Section: Birefringence Rheological Behavior and Spinnability Of Go Dmentioning
confidence: 99%